Portable Impedance Spectrometer for Characterizing the Electrical Properties of Dielectric Materials Using A Goertzel Filter - M Zikri Arifin; Mairizwan Mairizwan; Asrizal Asrizal; Mona Sari (Journal of Experimental and Applied Physics, 2026)
Dielectric materials have the ability to store large amounts of electrical energy, which is useful in electronics, such as in the manufacture of capacitors. However, the equipment available for characterization is usually quite complex and expensive. Therefore, this study aims to develop a highly portable embedded impedance spectrometer for characterizing the electrical properties of dielectric materials, namely complex permittivity and dissipation factor, and then demonstrate the effect of increasing the test frequency on the measurement results. The system consists of an STM32F407 microcontroller, an AD9850 DDS as an AC signal generator, and a Goertzel filter algorithm for signal processing. The results of testing the system with paper dielectric samples showed an accuracy of 89.37% for real impedance and 93.22% for imaginary impedance. The results of the paper dielectric sample characterization show an increase in the real value of complex permittivity in the 1kHz-10kHz frequency range, while the imaginary value shows an increase from 1kHz-5kHz and then stabilizes up to 10kHz. The increase in frequency also shows an increase in the dissipation factor (dielectric loss) at each increase in frequency